e-Course for Microsoft Office. (Cambridge, Massachusetts : Course Technology Cengage Learning, 1997)
e-Course is a new, fun way to learn how to use microcomputer applications, such as word processing and spreadsheets. Each e-Course product -- let's take Excel, for example -- is a CD and a Worktext that together teach you how to use computers in a way you have never been thought before.
Techtalk -- Study Plans -- Microsoft Word -- Word Processing e-Ssentials -- Tutorial. Word Basics -- Tutorial 2.Develop and Edit Documents -- Tutorial 3. Format Document Text and Tables -- Tutorial 4. Format Pages of a Document -- Microsoft Excel -- Spreadsheet e-Ssentials -- Tutorial 1. Spreadsheet Basics -- Tutorial 2. Create Simple Worksheets -- Tutorial 3. Format a Worksheet -- Tutorial 4. Create Charts -- Microsoft Access -- Database e-Ssentials -- Tutorial 1. Access Basics --Tutorial 2. Finding Information in a Database -- Tutorial 3. Database Reports and Graphs -- Tutorial 4. Creating a Database -- Microsoft Powerpoint -- Presentation e-Ssentials -- Tutorial 1. Powerpoint Basics -- Tutorial 2. Powerpoint Graphics, Charts, and Tableas.
Keywords: MICROSOFT OFFICE